Effectiveness of subsidized fertilizer distribution to rice farmer In Lemoe, Bacukiki District, Parepare, South Sulawesi. Issue 3 (July 2021) - Rukka, R M; Darma, R; Rukmana, D; Arsyad, M; Anriany, N P; Alwi, L
Abstract: Subsidized fertilizer is one of the government's efforts to ensure the availability of fertilizer. However, farmers have difficulty in accessing subsidized fertilizers. This study aims to find out the effectiveness of subsidized fertilizer distribution in Lemoe Village, Bacukiki District, Parepare City. The analysis method used is descriptive quantitative by using effectiveness analysis. The results showed that the distribution process there are 4 lines of fertilizer storage up to farmers. Subsidized fertilizer distribution is carried out in a closed system based on the Definitive Plan of Group Needs (RDKK) with the Highest Retail Price (HET) as stipulated in the Regulation of the Minister of Agriculture on Allocation and HET of Subsidized Fertilizer in the Agricultural Sector. Overall the distribution of fertilizer felt by farmers runs effectively, with this it can be known that the subsidized fertilizer distribution program in Lemoe Village, Bacukiki District, Parepare City has been implemented in accordance with the guidelines for the implementation of fertilizer subsidies.